The iron status of South African blood donors: balancing donor safety and blood demand. Issue 1 (1st November 2018) - van den Berg, Karin; Swanevelder, Ronel; Ingram, Charlotte; Lawrie, Denise; Glencross, Deborah Kim; Hilton, Caroline; Nieuwoudt, Martin
Abstract : BACKGROUND: Several studies in developed countries have demonstrated high levels of iron deficiency (ID) among blood donors. There is a paucity of data for developing countries where blood shortages remain a major concern. STUDY DESIGN AND METHODS: A total of 4412 donors were enrolled in the study. Specimens were collected for full blood count, iron, transferrin saturation, and ferritin assessment. Donor demographics were recorded. ID was indicated by a ferritin level of less than 20 ng/mL for men and less than 12 ng/mL for women. Anemia was defined as hemoglobin levels less than 12.5 g/dL. Regression models for predictors of ID were developed. RESULTS: A total of 17.5% of all donors had ID, with 16.3% prevalence in women and 18.6% in men. Low hemoglobin had the highest association with ID (adjusted odds ratio [AOR], 11.078; 95% confidence interval [CI], 7.915–15.505); male donors had twice the odds of ID compared to female donors (AOR, 2.501; 95% CI, 1.964–3.185), while increasing age was associated with lower odds (AOD, 0.965; 95% CI, 0.956–0.975). Among male donors, an interdonation interval of less than 3 months (AOR, 2.679; 95% CI, 1.929–3.720) was associated with ID. Compared to other females combined, colored female donors (AOR, 2.335; 95% CI, 1.310–4.160) had higher odds and black female donors (AOR, 0.559; 95% CI, 0.369–0.845) lower odds of ID. CONCLUSION: ID is common among South African donors; low hemoglobin, gender, ethnicity, and past donation history is independently associated with ID. Recommendations aimed at protecting donor health may increase blood shortages in South Africa.